In vitro effects of nitric oxide donors on apoptosis and oxidative/nitrative protein modifications in ADP-activated platelets - ŞENER, AZİZE; RABUŞ, ŞULE (SAGE PUBLICATIONS LTD, 2013)
Nitric oxide (NO) is an important physiological signaling molecule. However, when produced in excessive amounts, NO can also have toxic effects. The aim of this study is to investigate the effects of exogenous- and endogenous-derived NO on oxidative modifications of proteins and apoptosis in activated platelets. Washed platelets were incubated with L-arginine or nitroso-glutathione (GSNO) in the presence of adenosine diphosphate (ADP). After incubation, caspase-3 activity, phosphatidylserine (PS) externalization and the potential of mitochondrial membrane as markers of apoptosis were measured. In addition, the alterations in protein carbonylation (PCO) and nitrotyrosine (NT) formation as markers of protein oxidation were examined. Platelet activation with ADP (20 p,M) significantly increased PCO and NT levels and apoptotic events. After incubation with L-arginine, platelet NO production increased significantly. This L-arginine-induced increase caused decreases in formerly increased PCO and NT levels associated with ADP-induced platelet activation. Stimulation of NO production with L-arginine protected platelets from apoptosis. GSNO caused an increase in protein NT levels. Despite this change, GSNO was effective in inhibition of P-selectin expression, platelet aggregation, protein carbonylation and apoptosis. The results suggest that L-arginine and GSNO-mediated NO leads to the inhibition of key apoptotic processes including caspase-3 activation, PS exposure and low mitochondrial membrane potential in washed platelets. The inhibitory effect of platelet clearance of L-arginine and GSNO may be a novel useful therapeutic property in clinical application.
Keywords: Nitric oxide; apoptosis; protein oxidation; L-arginine; nitroso-glutathione; platelet; L-ARGININE; S-NITROSOGLUTATHIONE; OXIDATIVE STRESS; NEURONAL CELLS; INHIBITION; SYNTHASE; NITRATION; EXPRESSION; PEROXYNITRITE; RELEASE